Mapping gendered spatialities in leisure: the case of new consumption spaces in the city of Kolkata. Issue 4 (2nd October 2017) - Paul, Tanusree
Abstract : The subject of 'leisure', although extensively studied by scholars of multiple disciplines, has often lacked systematic theorization, so far as gendered spatialities are concerned. This paper attempts to address this gap by exploring how space and place relate to gendered leisure practices. Based on a primary survey in the city of Kolkata, India, this paper explores both the place-specific conditions and the person-specific experiences of leisure in the context of new consumption spaces (NCSs). The paper observes that, although these spaces have provided women with new 'freedom' to stroll around in public spaces by providing 'safe' and 'civil' environs, one should refrain from an unproblematic interpretation of this freedom. This is because the usual constraints on women's leisure continue to apply, even as they 'freely' engage with NCSs to spend their leisure time. Local cultural specificities get invested within these 'global' spaces and continue to define the 'appropriateness' of place, time, and company for women to be enjoying their leisure in their own right. Thus, these spaces actively participate in the reproduction of existential gendered realities and lived experiences, albeit tacitly.